Analisis Pemanfaatan Media Daring dalam Pembelajaran Matematika Ditinjau dari Kemandirian Belajar Siswa di Kelas XI SMAN 1 Koto Balingka - Armiati Armiati; Yanrizawati Yanrizawati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
Covid pandemic 19 has had a huge impact on education. Large-scale social restrictions make learning only possible at home. Teachers must have alternative means so that learning can be carried out so that learning objectives can be achieved properly. One of the learning media that can be used is learning media through the internet network (online). Online media that can be used include whatsapp, google classroom, zoom, etc. The purpose of this study is to see whether learning through online media can be carried out well in class XI of SMAN 1 Koto Balingka. This research is a descriptive study, literature study and survey method through the analysis of learning documents such as assignments and achievement of students carrying out the tasks given through whatsapp online media. The results of this study are through analysis it can be seen that learning conducted through online is less well implemented because of the internet network constraints where students live less well and burdened students with internet quotas and the still presence of students do not yet have the means for online learning.